Amniotic band syndrome at 14 weeks of gestation: a case report and literature review - N, Lalitha; Abraham, Reena; G, Umamaheswari (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Amniotic band syndrome comprises of a group of congenital anomalies involving the limbs, trunk, head and face characterised by asymmetry of involvement and varying severity. While mild variants have a good prognosis with normal life expectancy, severe cases may be incompatible with life. It is sporadic in occurrence with many theories postulated towards the pathogenesis. We report a case of amniotic band syndrome diagnosed at 14 weeks gestation in a 22 year old low risk primigravida-the foetus was seen as an amorphous mass with multiple anomalies, confirmed by autopsy. While early ultrasound helped detect lethal anomalies, correlation with autopsy provided an insight into possible disruptions in early foetal development leading to the various anomalies.